À terceira margem, a terceira imagem: os afetos triangulares nas narrativas de Carola Saavedra - Maria Fernanda Garbero de Aragão (Estudos de Literatura Brasileira Contemporânea)
The present article proposes a reading of affective relations in the analysis of three novels by the writer Carola Saavedra, Toda terça (2007), Flores azuis (2008) and Paisagem com dromedário (2010), here understood as a project of a trilogy of affections. The object of affection, the protagonist of these stories, recreates itself in a porosity feasible to its emergence in a "third bank", which lends the imagined place to its images to projections experienced by the characters. Indeed, a new spa- tial-affectionate dimension is recorded in the floor plan where the author builds reports about the affection, as well as the space, which also reveals a constitutive instability of its “non place”.